2016
DOI: 10.7791/jspmee.5.153
|View full text |Cite
|
Sign up to set email alerts
|

レーザ加工により表面微細構造を作製した鉄基板と液体Bi、In およびSn の濡れ性

Abstract: We found that the laser irradiated surface of copper substrate becomes fine structure, which we named "surface fine crevice structure". Liquid bismuth on "surface fine crevice structure" of copper substrate occurs "unusual wetting". In the present work, we investigated the wettability of "surface fine crevice structure" of iron substrate by liquid tin, indium and bismuth. "Unusual wetting" appears on laser irradiated surface of iron substrate in case of liquid indium and tin. Whereas, liquid bismuth does not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…We have previously reported on the morphologies of surface fine crevice structures created by laser irradiation of Cu and Fe surfaces. 1,3) Such surface structures enable super-spread wetting of liquid Bi, Sn on solid Cu and also wetting of liquid Sn, In on solid Fe. Furthermore, we were able to join Cu to Cu through microjoining without a solder fillet formation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on the morphologies of surface fine crevice structures created by laser irradiation of Cu and Fe surfaces. 1,3) Such surface structures enable super-spread wetting of liquid Bi, Sn on solid Cu and also wetting of liquid Sn, In on solid Fe. Furthermore, we were able to join Cu to Cu through microjoining without a solder fillet formation.…”
Section: Introductionmentioning
confidence: 99%
“…These pores are thought to be connected with each other to form a three-dimensional network porous structure, which is a factor that contributes to the in ltration of liquid Bi at the start of the unusual wetting on the surface ne crevice structure of Cu. In the previous works 4,6) , the existence of oxide in surface ne crevice structure is regarded as sort of factor interfering with the unusual wetting because it is generally known that the wettability of oxide by liquid metal is bad. From the above results, it was identi ed that the oxide generated by laser-irradiation is changed into the ne porous structure under reduction condition during wetting experiment to work as an important contributor to the unusual wetting.…”
Section: Formation Of Ne Porous Structurementioning
confidence: 99%
“…Unusual wetting is a phenomenon in which a liquid metal shows spreading wetting on ne complicated surface structures of metal by capillary action [1][2][3][4][5][6] . Originally, Tanaka and coworkers [1][2][3] found that unusual wetting occurs on the surface ne porous structure formed by treating atmospheric oxidation-reduction for metal surface, and reported that unusual wetting have a potential to achieve a joining with minimum overlay formation in brazing and soldering.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations